A Ru-M@Al-MCM-41 catalyst and its preparation method and application

By preparing the Ru-M@Al-MCM-41 catalyst, the active component Ru and the auxiliary component M are confined within the pores of the molecular sieve, which solves the problems of large precious metal usage and harsh reaction conditions in existing catalysts, achieves efficient preparation of hydrogenated pyromellitic tetracarboxylic acid esters, reduces production costs, and is suitable for industrial applications.

CN119608220BActive Publication Date: 2025-09-30CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311173192.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-09-30
Estimated Expiration
2043-09-12

Smart Images

  • Figure CN119608220B_ABST
    Figure CN119608220B_ABST
Patent Text Reader

Abstract

The present invention discloses a Ru-M@Al-MCM-41 catalyst and its preparation method and application. The present invention uses microspherical Al-MCM-41 as a carrier, confines the active component Ru and the auxiliary component M in the molecular sieve pores by strong electrostatic adsorption, and then reduces to obtain the Ru-M@Al-MCM-41 catalyst; the catalyst morphology is porous spherical. The Ru-M@Al-MCM-41 catalyst of the present invention has high activity and high stability and has good industrial application prospects. The catalyst of the present invention is used to catalyze the hydrogenation of pyromellitic acid esters to prepare hydrogenated pyromellitic acid esters, and the conversion rate of the substrate pyromellitic acid ester is high, and the selectivity of the target product hydrogenated pyromellitic acid ester is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalyst preparation, and in particular relates to a Ru-M@Al-MCM-41 catalyst and a preparation method and application thereof. Background Art

[0002] Currently, the primary use of hydrogenated pyromellitic dianhydride, both domestically and internationally, is in the production of polyimide (PI), a new engineering plastic. This synthetic material, developed in the 1960s, is a colorless, transparent polyimide produced by reacting hydrogenated pyromellitic dianhydride with aromatic diamines such as para-diaminodiphenyl ether. PI exhibits excellent transparency and infusibility. Compared to other plastics, PI exhibits exceptional chemical resistance, abrasion resistance, radiation resistance, heat resistance, low moisture absorption, and excellent adhesion to metal and other substrates. It can be made into films, fibers, wire enamels, adhesives, laminates, and molded parts, earning it the nickname "golden film." It holds broad application prospects in high-tech fields such as microelectronics, automotive, optoelectronics, large-scale integrated circuits, flat-panel displays, aerospace, and semiconductor materials. For example: in the optical field, it is used as optical switch materials, passive or active waveguide materials, optical fibers, second-order nonlinear optical materials, optoelectronic packaging materials, photosensitive materials, filters, photorefractive materials and other related optoelectronic materials; in the electronics field, it is used as the substrate of organic electroluminescent displays (OLED), the substrate of liquid crystal displays, negative compensation films, liquid crystal orientation film materials, etc.; in the aerospace field, it is used as thermal control coating materials, antenna collector materials, antenna reflector materials, interlayer insulation films of solar panels, etc.

[0003] Hydrogenated pyromellitic dianhydride is an important organic synthesis intermediate and an intermediate for the development of new chemical materials and high-value-added fine chemical products. It is mainly used in laboratory research and development processes and chemical production processes. Currently, the preparation of hydrogenated pyromellitic dianhydride mainly includes the following steps:

[0004] 1. Catalytic hydrogenation of pyromellitic acid to prepare hydrogenated pyromellitic acid;

[0005] 2. Hydrogenated pyromellitic acid is dehydrated and cyclized to prepare hydrogenated pyromellitic dianhydride.

[0006] The key technology for the preparation of hydrogenated pyromellitic dianhydride lies in the preparation of hydrogenated pyromellitic acid. Hydrogenated pyromellitic acid is primarily produced through the catalytic hydrogenation of pyromellitic acid or by hydrogenating pyromellitic esters to form hydrogenated pyromellitic esters, which are then hydrolyzed to produce hydrogenated pyromellitic acid. Both processes fall under the category of aromatic hydrogenation and benzene ring saturation hydrogenation. Currently, the hydrogenation process primarily utilizes precious metal catalysts, with reaction temperatures ranging from 50°C to 350°C and hydrogen pressures ranging from 1 to 30 MPa, using either batch reactors or continuous fixed-bed reactors.

[0007] EP1323700 adopts pyromellitic acid as raw material, and 5%Rh / C catalyst is hydrogenated in batch reactor, and catalyst initial activity and selectivity are higher, but the reusability of catalyst is lower, and activation treatment must be frequently carried out, which has greatly increased production cost.JP2006083080 and JP200863263 also all adopt rhodium as active component, but the life-span of catalyst is low.CN102105428 adopts palladium metal and rhodium metal mixed catalyst catalytic hydrogenation pyromellitic acid, but its reaction conditions are harsh, and required hydrogen pressure is at least more than 8MPa, has proposed higher requirement to reaction unit, and equipment investment is large during industrialization.JPA2006045166 adopts pyromellitic ester as raw material, and Ru / C catalyst carries out hydrogenation reaction synthesis hydrogenation pyromellitic ester, and it shows good catalytic performance, but its hydrogenation reaction required pressure is higher, generally more than 10MPa, and reaction conditions are harsh, is unfavorable for large-scale production. CN104926649 uses Ru-Pd noble metal as the active component and Ce as an auxiliary agent loaded on activated carbon. The catalyst can effectively reduce the reaction pressure, but the reaction temperature is high and the catalyst dosage is large, resulting in excessive initial investment costs.

[0008] The synthesis of hydrogenated tetramethyl pyromellitic acid by hydrogenating tetramethyl pyromellitic acid and then hydrolyzing it to prepare hydrogenated pyromellitic acid has a higher yield. However, the current catalysts all use precious metals such as Rh, Pd, Pt, Ru, etc. as active components, and the catalyst dosage is large, which is not conducive to industrial production.

[0009] Therefore, it is necessary to design and develop catalysts with low precious metal content that are more conducive to industrial production. Summary of the Invention

[0010] Purpose of the Invention: The present invention addresses the deficiencies of the prior art and provides a Ru-M@Al-MCM-41 catalyst, its preparation method, and its application. The Ru-M@Al-MCM-41 catalyst prepared in this method exhibits high activity and stability, and has promising industrial applications. The catalyst is used to catalyze the hydrogenation of pyromellitic acid esters to produce hydrogenated pyromellitic acid esters, achieving high conversion of the substrate pyromellitic acid ester and high selectivity for the target product, hydrogenated pyromellitic acid ester.

[0011] Technical solution: The purpose of the present invention is achieved through the following technical solution:

[0012] The present invention provides a Ru-M@Al-MCM-41 catalyst, which adopts microspherical Al-MCM-41 as a carrier, confines the active component Ru and the auxiliary component M in the molecular sieve pores by a strong electrostatic adsorption method, and then reduces to obtain the Ru-M@Al-MCM-41 catalyst; the catalyst morphology is porous spherical.

[0013] Preferably, the auxiliary component M is any one of W, Cr, Zr, Co, La or Ce.

[0014] Preferably, the mass ratio of the Al-MCM-41 carrier to the active component Ru is 1:0.02-0.05; the mass ratio of the Al-MCM-41 carrier to the auxiliary component M is 1:0.005-0.025.

[0015] The present invention also provides a method for preparing the above-mentioned Ru-M@Al-MCM-41 catalyst, comprising the following steps:

[0016] (1) Preparation of Al-MCM-41 support: Weigh the template agent CTABr in distilled water, add urea solution, and heat to a high temperature; add triethanolamine solution, keep heating and stirring, dropwise add TEOS, then add sodium aluminate solution, heat to reflux, centrifuge, filter, wash, dry, and calcine to obtain Al-MCM-41 support;

[0017] (2) Preparation of Ru-M@Al-MCM-41 catalyst: Ru(NH3)6Cl3 and M metal salt were weighed and dissolved in deionized water. NH3·H2O was added dropwise. Al-MCM-41 carrier was added. The catalyst was ultrasonicated, stirred, filtered, washed with water, washed with alcohol, dried, and calcined to obtain Ru-W@Al-MCM-41-10 catalyst.

[0018] Preferably, in step (1), the mass ratio of TEOS to CTABr is 1:0.1-0.2, and the concentration of CTABr is 0.01-0.02 g / mL.

[0019] Preferably, in step (1), the mass ratio of TEOS to urea is 1:1-2, and the urea concentration is 0.1-0.2 g / mL.

[0020] Preferably, in step (1), the mass ratio of TEOS to triethanolamine is 1:0.01-0.03, and the concentration of triethanolamine is 0.01-0.03 g / mL.

[0021] Preferably, in step (1), the mass ratio of TEOS to sodium aluminate is 1:0.03-0.05, and the concentration of sodium aluminate is 0.015-0.025 g / mL.

[0022] Preferably, in step (1), the heating temperature is 70-90° C., the stirring speed is 60-100 r / min, and the reflux time is 6-10 h.

[0023] Preferably, in step (2), the M metal salt is selected from H 28 N6O 41 W 12, any one of Cr(NO3)3·6H2O, Co(NO3)2·6H2O, Ce(NO3)3·6H2O, La(NO3)3·6H2O or ZrOCl2·8H2O.

[0024] Preferably, in step (2), NH3·H2O is added dropwise to make the pH value of the solution 11.5.

[0025] Preferably, in step (2), the mass ratio of the Al-MCM-41 carrier to Ru(NH3)6Cl3 is 1:0.06-0.15.

[0026] Preferably, in step (2), the mass ratio of the Al-MCM-41 carrier to the M metal salt is 1:0.009-0.2.

[0027] Preferably, in step (2), the mass ratio of the Al-MCM-41 carrier to deionized water is 1:150-250.

[0028] Preferably, in step (2), the ultrasonic time is 0.5 to 4 hours, and the stirring time is 4 to 8 hours.

[0029] The present invention also provides the use of the Ru-M@Al-MCM-41 catalyst in catalyzing the synthesis of hydrogenated pyromellitic acid ester from pyromellitic acid ester.

[0030] A preferred embodiment of the present invention is that the specific steps of catalyzing pyromellitic acid ester to synthesize hydrogenated pyromellitic acid ester are as follows: the Ru-M@Al-MCM-41 catalyst, pyromellitic acid ester and solvent are sequentially added to a reactor, the air in the reactor is replaced with hydrogen, the reactor is pressurized and heated to the reaction temperature before starting the reaction, and the catalyst is separated by centrifugation after the reaction is completed.

[0031] Further preferably, the mass ratio of the pyromellitic acid ester to the Ru-M@Al-MCM-41 catalyst is 1:0.03-0.05; the mass ratio of the pyromellitic acid ester to the solvent is 1:15-30; the reaction temperature is 80-100°C, the hydrogen pressure is 4-6 MPa, and the reaction time is 3-6 h.

[0032] Furthermore, the solvent is selected from one or more of methanol, ethanol, isopropanol, ethyl acetate or DMF.

[0033] Beneficial effects:

[0034] (1) The Ru-M@Al-MCM-41 catalyst synthesis method provided by the present invention has the advantages of simple equipment, convenient operation, mild conditions, and the confined structure enhances the recyclability of the catalyst. The process is environmentally friendly and conducive to large-scale production.

[0035] (2) The Ru-M@Al-MCM-41 catalyst provided by the present invention is a precious metal catalyst. Compared with existing precious metal catalysts, it has a lower precious metal loading, reduces production costs, and is more conducive to industrial production.

[0036] (3) The Ru-M@Al-MCM-41 catalyst provided by the present invention is used to catalyze the synthesis of hydrogenated pyromellitic acid esters from pyromellitic acid esters, with high conversion rate and selectivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is the SEM image of Ru-W@Al-MCM-41-1 prepared in Example 1.

[0038] Figure 2 This is the particle size distribution diagram of Ru-W@Al-MCM-41-1 prepared in Example 1.

[0039] Figure 3 This is the TEM spectrum of Ru-W@Al-MCM-41-1 prepared in Example 1. DETAILED DESCRIPTION

[0040] The technical solution of the present invention is described in detail below through specific embodiments, but the protection scope of the present invention is not limited to the embodiments.

[0041] If no specific techniques or conditions are specified in the examples, the experiments were carried out according to the techniques or conditions described in the literature in the field or according to the product instructions. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased through regular channels.

[0042] The experimental methods in the following examples are conventional methods unless otherwise specified. The experimental materials used in the following examples are commercially available products unless otherwise specified.

[0043] Example 1

[0044] Step 1: First, weigh 0.3g of the template agent CTABr and dissolve it in distilled water to prepare an aqueous solution with a concentration of C(CTABr) = 0.015g / mL. Stir at room temperature until the solution becomes clear and transparent. Add 30mL of 0.1g / mL urea solution to the above solution and heat it to 85°C. Add 2mL of 0.01g / mL triethanolamine solution and heat and stir at 80r / min for 15min. Add 2g of TEOS dropwise and stir for 30min. Then add 4mL of 0.02g / mL sodium aluminate solution and heat under reflux for 8h. The resulting product is centrifuged, filtered, washed, and dried. The dried sample is placed in a muffle furnace and calcined at 550°C for 3h (heating rate of 2°C / min) to obtain the Al-MCM-41 carrier. The mass ratio of TEOS to CTABr is 1:0.15, the mass ratio of TEOS to urea is 1:1.5, the mass ratio of TEOS to triethanolamine is 1:0.01, and the mass ratio of TEOS to sodium aluminate is 1:0.04.

[0045] Step 2: Weigh 0.009g of Ru(NH3)6Cl3, 0.002g of H 28 N6O 41 W 12 Place 20g of deionized water in a 50mL beaker, add NH3·H2O dropwise to a pH of 11.5, and sonicate for 0.5h. Add 0.1g of the Al-MCM-41 support from step 1 to this solution and stir for 6h. Filter, wash with water, then with alcohol, and vacuum dry at 60°C overnight, then at 120°C for 4h. Reduce the mixture at 400°C in a 10% H2 / Ar gas mixture for 2h to obtain the Ru-W@Al-MCM-41 catalyst. This catalyst is designated Ru-W@Al-MCM-41-1.

[0046] The mass ratio of the Al-MCM-41 carrier to the active component Ru is 1:0.03, and the mass ratio of the Al-MCM-41 carrier to the auxiliary component W is 1:0.015.

[0047] SEM characterization of Ru-W@Al-MCM-41-1 Figure 1 The particle size distribution diagram is shown in Figure 2 As shown. Figure 1 、 Figure 2 It can be seen that the particle size of the Ru-W@Al-MCM-41-1 catalyst is uniform, highly dispersed, and the average diameter of the nanospheres is about 100 nm.

[0048] TEM characterization of Ru-W@Al-MCM-41-1 is as follows Figure 3As shown in the TEM image, after loading the Ru-W nanoparticles, the Al-MCM-41 mesoporous molecular sieve still exhibits a highly dispersed microspherical morphology, with the pores intact and evenly distributed, exhibiting an ordered mesoporous structure. A 5nm magnified TEM image of the Ru-W@Al-MCM-41-1 catalyst shows that after loading the Ru-W nanoparticles, no obvious Ru-W nanoparticles are found on the surface of the support, indicating that the Ru-W nanoparticles have entered the pores of the molecular sieve.

[0049] Example 2

[0050] Step 1: First, weigh 0.3g of the template agent CTABr and dissolve it in distilled water to prepare an aqueous solution with a concentration of C(CTABr) = 0.015g / mL. Stir at room temperature until the solution becomes clear and transparent. Add 30mL of 0.1g / mL urea solution to the above solution and heat it to 90°C. Add 2mL of 0.015g / mL triethanolamine solution and heat and stir at 80r / min for 15min. Add 2g of TEOS dropwise and stir for 30min. Then add 4mL of 0.02g / mL sodium aluminate solution and heat under reflux for 10h. The resulting product is centrifuged, filtered, washed, and dried. The dried sample is placed in a muffle furnace and calcined at 550°C for 3h (heating rate of 2°C / min) to obtain the Al-MCM-41 carrier. The mass ratio of TEOS to CTABr is 1:0.15, the mass ratio of TEOS to urea is 1:1.5, the mass ratio of TEOS to triethanolamine is 1:0.015, and the mass ratio of TEOS to sodium aluminate is 1:0.04.

[0051] Step 2: Weigh 0.009g of Ru(NH3)6Cl3, 0.0013g of H 28 N6O 41 W 12 Place 20g of deionized water in a 50mL beaker, add NH3·H2O dropwise to a pH of 11.5, and sonicate for 1h. Add 0.1g of the Al-MCM-41 support from step 1 to this solution and stir for 6h. Filter, wash with water, then with alcohol, and vacuum dry at 60°C overnight, then at 120°C for 4h. Reduce the mixture at 400°C in a 10% H2 / Ar gas mixture for 2h to obtain the Ru-W@Al-MCM-41 catalyst. This catalyst is designated Ru-W@Al-MCM-41-2.

[0052] The mass ratio of the Al-MCM-41 carrier to the active component Ru is 1:0.03, and the mass ratio of the Al-MCM-41 carrier to the auxiliary component W is 1:0.01.

[0053] Example 3

[0054] Step 1: First, weigh 0.2g of the template agent CTABr and dissolve it in distilled water to prepare an aqueous solution with a concentration of C(CTABr) = 0.01g / mL. Stir at room temperature until the solution becomes clear and transparent. Add 20mL of 0.1g / mL urea solution to the above solution and heat it to 70°C. Add 2mL of 0.01g / mL triethanolamine solution and heat and stir at 60r / min for 15min. Add 2g of TEOS dropwise and stir for 30min. Then add 4mL of 0.015g / mL sodium aluminate solution and heat under reflux for 6h. The resulting product is centrifuged, filtered, washed, and dried. The dried sample is placed in a muffle furnace and calcined at 550°C for 3h (heating rate of 2°C / min) to obtain the Al-MCM-41 carrier. The mass ratio of TEOS to CTABr is 1:0.1, the mass ratio of TEOS to urea is 1:1, the mass ratio of TEOS to triethanolamine is 1:0.01, and the mass ratio of TEOS to sodium aluminate is 1:0.03.

[0055] Step 2: Weigh 0.015g of Ru(NH3)6Cl3, 0.02g of Cr(NO3)3·6H2O, and 25g of deionized water into a 50mL beaker. Add NH3·H2O dropwise to a pH of 11.5 and sonicate for 1h. Add 0.1g of the Al-MCM-41 support from Step 1 to this solution and stir for 8h. Filter, wash with water, then with alcohol, and vacuum dry at 60°C overnight, then at 120°C for 4h. Reduce the mixture at 400°C for 2h in a 10% H2 / Ar mixture to obtain the Ru-Cr@Al-MCM-41 catalyst. This catalyst is designated Ru-Cr@Al-MCM-41.

[0056] The mass ratio of the Al-MCM-41 carrier to the active component Ru is 1:0.05, and the mass ratio of the Al-MCM-41 carrier to the auxiliary component Cr is 1:0.025.

[0057] Example 4

[0058] Step 1: First, weigh 0.4g of the template agent CTABr and dissolve it in distilled water to prepare an aqueous solution with a concentration of C(CTABr) = 0.02g / mL. Stir at room temperature until the solution becomes clear and transparent. Add 20mL of 0.2g / mL urea solution to the above solution and heat it to 90°C. Add 2mL of 0.02g / mL triethanolamine solution and heat and stir at 100r / min for 15min. Add 2g of TEOS dropwise and stir for 30min. Then add 4mL of 0.025g / mL sodium aluminate solution and heat under reflux for 10h. The resulting product is centrifuged, filtered, washed, and dried. The dried sample is placed in a muffle furnace and calcined at 550°C for 3h (heating rate of 2°C / min) to obtain the Al-MCM-41 carrier. The mass ratio of TEOS to CTABr is 1:0.2, the mass ratio of TEOS to urea is 1:2, the mass ratio of TEOS to triethanolamine is 1:0.02, and the mass ratio of TEOS to sodium aluminate is 1:0.05.

[0059] Step 2: Weigh 0.006g of Ru(NH3)6Cl3, 0.0025g of Co(NO3)2·6H2O, and 15g of deionized water into a 50mL beaker. Add NH3·H2O dropwise to a pH of 11.5 and sonicate for 0.5h. Add 0.1g of the Al-MCM-41 support from Step 1 to the solution and stir for 4h. Filter, wash with water, then with alcohol, and vacuum dry at 60°C overnight, then at 120°C for 4h. Reduce the solution at 400°C for 2h in a 10% H2 / Ar mixture to obtain the Ru-Co@Al-MCM-41 catalyst. This catalyst is designated Ru-Co@Al-MCM-41.

[0060] The mass ratio of the Al-MCM-41 carrier to the active component Ru is 1:0.02, and the mass ratio of the Al-MCM-41 carrier to the auxiliary component Co is 1:0.005.

[0061] Example 5

[0062] Step 1: First, weigh 0.3g of the template agent CTABr and dissolve it in distilled water to prepare an aqueous solution with a concentration of C(CTABr) = 0.015g / mL. Stir at room temperature until the solution becomes clear and transparent. Add 20mL of 0.15g / mL urea solution to the above solution and heat it to 80°C. Add 2mL of 0.015g / mL triethanolamine solution and heat and stir at 80r / min for 15min. Add 2g of TEOS dropwise and stir for 30min. Then add 4mL of 0.02g / mL sodium aluminate solution and heat under reflux for 8h. The resulting product is centrifuged, filtered, washed, and dried. The dried sample is placed in a muffle furnace and calcined at 550°C for 3h (heating rate of 2°C / min) to obtain the Al-MCM-41 carrier. The mass ratio of TEOS to CTABr is 1:0.15, the mass ratio of TEOS to urea is 1:1.5, the mass ratio of TEOS to triethanolamine is 1:0.015, and the mass ratio of TEOS to sodium aluminate is 1:0.04.

[0063] Step 2: Weigh 0.012g of Ru(NH3)6Cl3, 0.0032g of Ce(NO3)3·6H2O, and 20g of deionized water into a 50mL beaker. Add NH3·H2O dropwise to a pH of 11.5 and sonicate for 1h. Add 0.1g of the Al-MCM-41 support from Step 1 to this solution and stir for 6h. Filter, wash with water, then with alcohol, and vacuum dry at 60°C overnight, then at 120°C for 4h. Reduce the mixture at 400°C for 2h in a 10% H2 / Ar mixture to obtain the Ru-Ce@Al-MCM-41 catalyst. This catalyst is designated Ru-Ce@Al-MCM-41.

[0064] The mass ratio of the Al-MCM-41 carrier to the active component Ru is 1:0.04, and the mass ratio of the Al-MCM-41 carrier to the auxiliary component Ce is 1:0.01.

[0065] Example 6

[0066] Step 1: First, weigh 0.2g of the template agent CTABr and dissolve it in distilled water to prepare an aqueous solution with a concentration of C(CTABr) = 0.013g / mL. Stir at room temperature until the solution becomes clear and transparent. Add 30mL of 0.1g / mL urea solution to the above solution and heat it to 75°C. Add 1mL of 0.03g / mL triethanolamine solution and heat and stir at 90r / min for 15min. Add 2g of TEOS dropwise and stir for 30min. Then add 4mL of 0.025g / mL sodium aluminate solution and heat under reflux for 8h. The resulting product is centrifuged, filtered, washed, and dried. The dried sample is placed in a muffle furnace and calcined at 550°C for 3h (heating rate of 2°C / min) to obtain the Al-MCM-41 carrier. The mass ratio of TEOS to CTABr is 1:0.1, the mass ratio of TEOS to urea is 1:1.5, the mass ratio of TEOS to triethanolamine is 1:0.01, and the mass ratio of TEOS to sodium aluminate is 1:0.05.

[0067] Step 2: Weigh 0.009g of Ru(NH3)6Cl3, 0.0063g of La(NO3)3·6H2O, and 20g of deionized water into a 50mL beaker. Add NH3·H2O dropwise to a pH of 11.5 and sonicate for 0.5h. Add 0.1g of the Al-MCM-41 support from Step 1 to this solution and stir for 6h. Filter, wash with water, then with alcohol, and vacuum dry at 60°C overnight, then at 120°C for 4h. Reduce the mixture at 400°C for 2h in a 10% H2 / Ar mixture to obtain the Ru-La@Al-MCM-41 catalyst. This catalyst is designated Ru-La@Al-MCM-41.

[0068] The mass ratio of the Al-MCM-41 carrier to the active component Ru is 1:0.03, and the mass ratio of the Al-MCM-41 carrier to the auxiliary component La is 1:0.02.

[0069] Example 7

[0070] Step 1: First, weigh 0.4g of the template agent CTABr and dissolve it in distilled water to prepare an aqueous solution with a concentration of C(CTABr) = 0.02g / mL. Stir at room temperature until the solution becomes clear and transparent. Add 20mL of 0.2g / mL urea solution to the above solution and heat it to 85°C. Add 1.5mL of 0.03g / mL triethanolamine solution and heat and stir at 100r / min for 15min. Add 2g of TEOS dropwise and stir for 30min. Then add 4mL of 0.02g / mL sodium aluminate solution and heat under reflux for 10h. The resulting product is centrifuged, filtered, washed, and dried. The dried sample is placed in a muffle furnace and calcined at 550°C for 3h (heating rate of 2°C / min) to obtain the Al-MCM-41 carrier. The mass ratio of TEOS to CTABr is 1:0.2, the mass ratio of TEOS to urea is 1:2, the mass ratio of TEOS to triethanolamine is 1:0.015, and the mass ratio of TEOS to sodium aluminate is 1:0.04.

[0071] Step 2: Weigh 0.015g of Ru(NH3)6Cl3, 0.0054g of ZrOCl2·8H2O, and 25g of deionized water into a 50mL beaker. Add NH3·H2O dropwise to a pH of 11.5 and sonicate for 1 hour. Add 0.1g of the Al-MCM-41 support from Step 1 to this solution and stir for 8 hours. Filter, wash with water, then with alcohol, and vacuum dry at 60°C overnight, then at 120°C for 4 hours. Reduce the mixture at 400°C for 2 hours in a 10% H2 / Ar mixture to obtain the Ru-Zr@Al-MCM-41 catalyst. This catalyst is designated Ru-Zr@Al-MCM-41.

[0072] The mass ratio of the Al-MCM-41 carrier to the active component Ru is 1:0.05, and the mass ratio of the Al-MCM-41 carrier to the auxiliary component Zr is 1:0.015.

[0073] Comparative Example 1

[0074] Step 1: First, weigh 0.4g of the template agent CTABr and dissolve it in distilled water to prepare an aqueous solution with a concentration of C(CTABr) = 0.02g / mL. Stir at room temperature until the solution becomes clear and transparent. Add 20mL of 0.2g / mL urea solution to the above solution and heat it to 85°C. Add 2.0mL of 0.03g / mL triethanolamine solution and heat and stir at a speed of 100r / min for 15min. Add 2g of TEOS dropwise and stir for 30min. Then add 4mL of 0.02g / mL sodium aluminate solution and heat under reflux for 10h. The resulting product is centrifuged, filtered, washed, and dried. The dried sample is placed in a muffle furnace and calcined at 550°C for 3h (heating rate of 2°C / min) to obtain the Al-MCM-41 carrier. The mass ratio of TEOS to CTABr is 1:0.2, the mass ratio of TEOS to urea is 1:2, the mass ratio of TEOS to triethanolamine is 1:0.015, and the mass ratio of TEOS to sodium aluminate is 1:0.04.

[0075] Step 2: Weigh 0.015g of Ru(NH3)6Cl3 and 25g of deionized water into a 50mL beaker. Add NH3·H2O dropwise to a pH of 11.5 and sonicate for 1h. Add 0.1g of the Al-MCM-41 support from Step 1 to this solution and stir for 8h. Filter, wash with water, then with alcohol, and vacuum dry at 60°C overnight, then at 120°C for 4h. Reduce the mixture at 400°C for 2h in a 10% H2 / Ar gas mixture to obtain the Ru@Al-MCM-41 catalyst. This catalyst is designated Ru@Al-MCM-41.

[0076] The mass ratio of Al-MCM-41 carrier to active component Ru is 1:0.05.

[0077] Catalyst performance evaluation:

[0078] The Ru-M@Al-MCM-41 catalysts prepared in Examples 1-7 and the catalyst prepared in the comparative example were used to catalyze the synthesis of hydrogenated pyromellitic acid ester from pyromellitic acid ester.

[0079] Application Example 1

[0080] 1.0g of tetramethyl pyromellitate (TPM), 0.03g of Ru-W@Al-MCM-41-1 catalyst, and 20g of isopropanol (R20) were weighed in a raw material to catalyst ratio of 1:0.03 and a raw material to solvent ratio of 1:20. The mixture was then placed in an autoclave. The air in the autoclave was replaced three times with hydrogen. The pressure in the autoclave was then filled with hydrogen to 5 MPa. The stirring speed was adjusted to 600 rpm, and the temperature was raised to 80°C. The reaction was initiated and allowed to proceed for 3 hours. After completion, the catalyst was separated by centrifugation. Liquid chromatography analysis of the resulting liquid revealed a conversion of 99.60% and a selectivity of 95.95%.

[0081] Application Example 2

[0082] 1.0g of tetraethyl pyromellitate (TPY), 0.04g of Ru-W@Al-MCM-41-2 catalyst, and 30g of isopropanol (R2P) solvent) were weighed sequentially into an autoclave at a raw material to catalyst ratio of 1:0.04 and a raw material to solvent ratio of 1:30. The mixture was then placed into the autoclave. The air in the autoclave was replaced three times with hydrogen. The autoclave was then filled with hydrogen to a pressure of 5 MPa. The stirring speed was adjusted to 600 rpm, and the temperature was raised to 90°C. The reaction was initiated and allowed to proceed for 4 hours. After completion, the catalyst was separated by centrifugation. Liquid chromatography analysis of the resulting liquid revealed a conversion of 99.72% and a selectivity of 99.03%.

[0083] Application Example 3

[0084] 1.0g of tetramethyl pyromellitate (TMP), 0.05g of Ru-Cr@Al-MCM-41 catalyst, and 15g of methanol (RMS) were weighed sequentially (i.e., a raw material to catalyst mass ratio of 1:0.05 and a raw material to solvent mass ratio of 1:15). The mixture was then added to an autoclave. The air in the autoclave was displaced three times with hydrogen. The autoclave was then filled with hydrogen to a pressure of 4 MPa. The stirring speed was adjusted to 600 rpm, and the temperature was raised to 100°C. The reaction was initiated and allowed to proceed for 4 hours. After completion, the catalyst was separated by centrifugation. Liquid chromatography analysis of the resulting liquid revealed a conversion of 99.68% and a selectivity of 97.21%.

[0085] Application Example 4

[0086] 1.0g of tetraethyl pyromellitate (TPP), 0.03g of Ru-Co@Al-MCM-41 catalyst, and 30g of ethanol solvent were weighed sequentially (i.e., a raw material to catalyst mass ratio of 1:0.03 and a raw material to solvent mass ratio of 1:30). These were then added to an autoclave. The air in the autoclave was displaced three times with hydrogen. The autoclave was then filled with hydrogen to a pressure of 6 MPa. The stirring speed was adjusted to 600 rpm, and the temperature was raised to 80°C. The reaction was initiated and allowed to proceed for 5 hours. After completion, the catalyst was separated by centrifugation. Liquid chromatography analysis of the resulting liquid revealed a conversion of 99.52% and a selectivity of 95.83%.

[0087] Application Example 5

[0088] 1.0g of tetraethyl pyromellitate (TPP), 0.04g of Ru-Ce@Al-MCM-41 catalyst, and 30g of ethyl acetate (RMB:Ce@Al-MCM-41) were weighed in a 1:0.04 raw material to catalyst mass ratio and a 1:30 raw material to solvent mass ratio. The mixture was then placed in an autoclave. The air in the autoclave was replaced three times with hydrogen. The pressure in the autoclave was then filled with hydrogen to 5 MPa. The stirring speed was adjusted to 600 rpm, and the temperature was raised to 90°C. The reaction was initiated and allowed to proceed for 4 hours. After completion, the catalyst was separated by centrifugation. Liquid chromatography analysis of the resulting liquid revealed a conversion of 99.81% and a selectivity of 97.33%.

[0089] Application Example 6

[0090] 1.0g of tetrapropyl pyromellitate (TPP), 0.03g of Ru-La@Al-MCM-41 catalyst, and 20g of DMF solvent were weighed sequentially (i.e., a raw material to catalyst mass ratio of 1:0.03 and a raw material to solvent mass ratio of 1:20). These were then added to an autoclave. The air in the autoclave was replaced three times with hydrogen. The autoclave was then filled with hydrogen to a pressure of 4 MPa. The stirring speed was adjusted to 600 rpm, and the temperature was raised to 80°C. The reaction was initiated and allowed to proceed for 6 hours. After completion, the catalyst was separated by centrifugation. Liquid chromatography analysis of the resulting liquid revealed a conversion of 99.58% and a selectivity of 98.31%.

[0091] Application Example 7

[0092] 1.0 g of tetramethyl pyromellitate raw material, 0.05 g of Ru-Zr@Al-MCM-41 catalyst, and 15 g of isopropanol solvent were weighed sequentially, with a raw material to catalyst mass ratio of 1:0.05 and a raw material to solvent mass ratio of 1:15. These were then added to an autoclave. The air in the autoclave was replaced with hydrogen three times, and the autoclave was filled with hydrogen to a pressure of 4 MPa. The stirring speed was adjusted to 600 rpm, and the temperature was raised to 100°C. The reaction was initiated and allowed to proceed for 3 hours. After completion, the catalyst was separated by centrifugation. Liquid chromatography analysis of the resulting liquid revealed a conversion of 99.56% and a selectivity of 97.88%. The catalyst obtained by centrifugation was again evaluated as described in Application Example 7, revealing a conversion of 99.38% and a selectivity of 97.12%. After repeating this process three times, the conversion was 98.87% and the selectivity was 97.01%.

[0093] Application Example 8

[0094] 1.0 g of tetramethyl pyromellitate raw material, 0.05 g of Ru@Al-MCM-41 catalyst, and 15 g of isopropanol solvent were weighed sequentially, with a raw material to catalyst mass ratio of 1:0.05 and a raw material to solvent mass ratio of 1:15. These were then added to an autoclave. The air in the autoclave was replaced with hydrogen three times, and the autoclave was filled with hydrogen to a pressure of 4 MPa. The stirring speed was adjusted to 600 rpm, and the temperature was raised to 100°C. The reaction was initiated and allowed to proceed for 3 hours. After completion, the catalyst was separated by centrifugation. Liquid chromatography analysis of the resulting liquid revealed a conversion of 90.01% and a selectivity of 64.32%. The catalyst obtained by centrifugation was again evaluated as described in Application Example 8, with a conversion of 75.43% and a selectivity of 61.23%. After repeating this process three times, the conversion was 54.35% and the selectivity was 58.66%.

[0095] The experimental results of each application example are shown in Table 1:

[0096] Table 1 Application example experimental results

[0097]

[0098] As described above, although the present invention has been shown and described with reference to specific preferred embodiments, it should not be construed as limiting the present invention itself. Various changes may be made to it in form and detail without departing from the spirit and scope of the present invention as defined in the appended claims.

Claims

1. A Ru-M@Al-MCM-41 catalyst, characterized in that Using microspherical Al-MCM-41 as a carrier, the active component Ru and the auxiliary component M are confined within the molecular sieve pores by strong electrostatic adsorption, and then reduced to obtain the Ru-M@Al-MCM-41 catalyst; the catalyst has a porous spherical morphology; The auxiliary component M is any one of W, Cr, Zr, Co, La or Ce; The mass ratio of the Al-MCM-41 carrier to the active component Ru is 1:0.02-0.05; the mass ratio of the Al-MCM-41 carrier to the auxiliary component M is 1:0.005-0.

025.

2. The method for preparing the catalyst according to claim 1, wherein The following steps are involved: (1) Preparation of Al-MCM-41 carrier: Weigh the template CTABr in distilled water, add urea solution, and heat to a high temperature; add triethanolamine solution, keep heating and stirring, dropwise add TEOS, then add sodium aluminate solution, heat to reflux, centrifuge, filter, wash, dry, and calcine to obtain Al-MCM-41 carrier; (2) Preparation of Ru-M@Al-MCM-41 catalyst: Weigh Ru(NH3)6Cl3 and M metal salt in deionized water, add NH3·H2O dropwise, add Al-MCM-41 carrier, and obtain Ru-W@Al-MCM-41-10 catalyst by ultrasonication, stirring, filtering, water washing, alcohol washing, drying, and calcination reduction.

3. The preparation method according to claim 2, characterized in that In step (1), the mass ratio of TEOS to CTABr is 1:0.1-0.2, and the concentration of CTABr is 0.01-0.02 g / mL; the mass ratio of TEOS to urea is 1:1-2, and the concentration of urea is 0.1-0.2 g / mL; the mass ratio of TEOS to triethanolamine is 1:0.01-0.03, and the concentration of triethanolamine is 0.01-0.03 g / mL; the mass ratio of TEOS to sodium aluminate is 1:0.03-0.05, and the concentration of sodium aluminate is 0.015-0.025 g / mL; the heating temperature is 70-90°C, the stirring speed is 60-100 r / min, and the reflux time is 6-10 h.

4. The preparation method according to claim 2, characterized in that In step (2), the mass ratio of the Al-MCM-41 carrier to Ru(NH3)6Cl3 is 1:0.06~0.15, the mass ratio of the Al-MCM-41 carrier to the M metal salt is 1:0.009~0.2, and the mass ratio of the Al-MCM-41 carrier to deionized water is 1:150~250; the ultrasonic time is 0.5~4h, and the stirring time is 4~8h.

5. Use of the Ru-M@Al-MCM-41 catalyst according to claim 1 in catalyzing the synthesis of hydrogenated pyromellitic acid esters from pyromellitic acid esters.

6. The use according to claim 5, characterized in that The Ru-M@Al-MCM-41 catalyst, pyromellitic acid ester and solvent were sequentially added into the reactor. After the air in the reactor was replaced with hydrogen, the reactor was pressurized and heated to the reaction temperature before the reaction began. After the reaction was completed, the catalyst was separated by centrifugation.

7. The use according to claim 6, characterized in that The mass ratio of the pyromellitic acid ester to the Ru-M@Al-MCM-41 catalyst is 1:0.03-0.05; the mass ratio of the pyromellitic acid ester to the solvent is 1:15-30; the reaction temperature is 80-100° C., the hydrogen pressure is 4-6 MPa, and the reaction time is 3-6 h.

8. The use according to claim 6, characterized in that The solvent is selected from one or more of methanol, ethanol, isopropanol, ethyl acetate or DMF.